2002
DOI: 10.1002/ejsp.140
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of positive attitude as a function of subgroup and superordinate group identifications in intergroup contact

Abstract: The role of category salience in mediating the effects of intergroup contact was examined. One theoretical model proposes that some psychological salience of subgroup categories is necessary to facilitate the generalization of attitude change beyond the immediate contact situation. Another argues that a re-categorization of the subgroups into a new superordinate category is more beneficial, whilst a third suggests that de-categorizing the situation entirely is optimal. An alternative view, which combines the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 47 publications
16
166
2
7
Order By: Relevance
“…In addition, experimental interventions to induce different representations of groups have demonstrated that creating a dual identity can be just as effective as a one-group identity for reducing bias toward outgroup members present in the contact situation (González & Brown, 2003). Moreover, emphasizing dual identity can be even more effective than facilitating a one-group representation for improving attitudes toward the outgroup, beyond the specific intergroup contact situation, because the association between present outgroup members and the outgroup as a whole is maintained (González & Brown, 2003. However, when subgroups are recategorized within superordinate identity, they tend to show greater bias toward groups not included within that common ingroup identity (Davies, Steele, & Markus, 2008;Kessler & Mummendey, 2001).…”
Section: Limitations Of Common Ingroup Identity Modelmentioning
confidence: 99%
“…In addition, experimental interventions to induce different representations of groups have demonstrated that creating a dual identity can be just as effective as a one-group identity for reducing bias toward outgroup members present in the contact situation (González & Brown, 2003). Moreover, emphasizing dual identity can be even more effective than facilitating a one-group representation for improving attitudes toward the outgroup, beyond the specific intergroup contact situation, because the association between present outgroup members and the outgroup as a whole is maintained (González & Brown, 2003. However, when subgroups are recategorized within superordinate identity, they tend to show greater bias toward groups not included within that common ingroup identity (Davies, Steele, & Markus, 2008;Kessler & Mummendey, 2001).…”
Section: Limitations Of Common Ingroup Identity Modelmentioning
confidence: 99%
“…In fact, they claim that dual identity is a desirable configuration, as it implies sufficient identification with one's subgroup to experience basic security and sufficient identification with the overarching group to preclude divisiveness". (González & Brown, 2003;Gonzalez et al, 2009) The idea of dual identity could be used to understand the simultaneous sense of belonging both "here" and "there" that can be experienced by migrants both in the indigenous community of Buenavista and in the transmigrant community of (undocumented) Hispanic migrants in Seattle. Phinney and colleagues (2001) argue that when an immigrant arrives to a new country their attitudes towards whether or not to retain their origin country's culture is determined by the new host country.…”
Section: Having a Space Of Reflection And To Release Their Burdenmentioning
confidence: 99%
“…Dual identity interventions have been found to produce greater reductions in out-group bias than either superordinate-identity recategorization or decategorization interventions when group members attempt to differentiate themselves from an overly inclusive category (Dovidio et al 2007; and when group differences are salient (Gonzalez and Brown 2003;. Research has also found that dual-identity interventions work to reduce prejudice even when more salient group differences, such as national identity, are employed (e.g., "British" vs. "European"; Crisp, Stone and Hall 2006;"Arab" vs. "Jew", Saguy, Tausch, Dovidio and Pratto 2009) with small to medium standardized mean differences (c.f., Crisp et al 2006;Dovidio et al 2007;Brown 2003, 2006;Saguy et al 2009).…”
Section: Dual-identity Interventionsmentioning
confidence: 99%